STRENGTHENING DIGITAL VILLAGE TRANSFORMATION THROUGH ASSISTANCE WITH SMART VILLAGE INFORMATION SYSTEMS (SIDESA) AND SALT POTENTIAL MAPPING IN LEMBUNG VILLAGE, PAMEKASAN REGENCY - Umam, Busro Akramul; Darmawan, Aang Kisnu; Muqaddas, Zaiful; Kartini, Kartini; Daryanto, Eko; Anekawati, Anik; Makruf, Masdukil (International Journal of Engagement and Empowerment (IJE2), 2024)
Digital village transformation in Indonesia is crucial for improving government services, regional economies, and quality of life. The Indonesian government promotes this through policies like Village Regulation No. 8 on the Village Information System (SID). Mapping salt potential is also essential for effective resource management, environmental conservation, and reducing poverty. These initiatives aim to empower communities, enhance services, and foster economic growth. However, The implementation of Village Information Systems (SID) faces challenges due to lack of ICT infrastructure, low digital literacy among village officials, limited network connectivity, absence of electricity, and heavy workloads. Addressing these issues, enhancing digital literacy, and ensuring consistent network availability are crucial for efficient rural service delivery. This community service activity aims to (1)create a web-based Smart Village information system, (2)create a digital map of salt potential, (3)improve the skills of village officials in digital-based archive management and administration, (4)improve management and development of village potential by building an intelligent village information system (SIDESA) and a salt potential map. The output of this activity produces (1) a web-based intelligent village information system (SIDESA), (2) the official Lembung Village website, (3) a digital map of salt potential, and (4) a monograph book: GIS-based intelligent village information system. The Lembung Village, digital village transformation, has been successful, with the Smart Village Information System (SIDESA) and digital maps of salt potential being developed and used by village officials and the community. The average knowledge of SIDESA increased from 30% to 85% after training, and satisfaction with the system reached 90%. The digital map had a 95% accuracy rate, and the training and mentoring increased understanding to 82%. A monograph book was published, achieving 80% reader satisfaction